STUDY OF THE HYPOGLYCEMIC AND CARDIOPROTECTIVE EFFECT OF EMPAGLIFLOZIN IN THERAPY OF PATIENTS WITH TYPE 2 DIABETES MELLITUS (World Bulletin of Public Health, 2023)
The aim of our study was to study the hypoglycemic and cardioprotective effect of empagliflozin in patients with type 2 diabetes mellitus cardiovascular diseases
Keywords: type 2 diabetes mellitus; atherosclerotic cardiovascular disease; sodium glucose cotransporter type